PHENOTYPIC PLASTICITY OF BRONCHOPULMONARY EPITHELIUM IN THE DEVELOPMENT OF PULMONARY OSSIFICATION IN MINERS (ANALYTICAL REVIEW, ANALYSIS OF CLINICAL CASES, SUBSTANTIATION OF THE RESEARCH METHOD) - Бондарев, Олег Иванович; Бугаева, Мария Сергеевна; Уланова, Евгения Викторовна (Medicine in Kuzbass, 2024)
Osteoplastic pulmonopathy is an extremely rare but serious complication of occupational lung diseases, characterized by the formation of bone tissue in the lung parenchyma. This review is dedicated to studying the cellular mechanisms of osteoplastic pulmonopathy development in miners exposed to long-term effects of coal-rock dust, with particular attention to the role of phenotypic plasticity of the bronchopulmonary epithelium. This is a specific, relevant topic, taking into account the peculiarities of professional risks in mining activities. Objective of the review was to present current data on the extremely rare pathology of osteoplastic pulmonopathy as one of the variants that may be associated with the occupational pathology of miners. Conclusion. Literature data and our own observation, combined with the absence of radiological signs specific to osteoplastic pulmonopathy and the possibility of its clinically asymptomatic course, give reason to assume a wider prevalence of osteoplastic pulmonopathy, which in workers of dust professions may occur under the guise of lung calcification, being, in fact, a form of pneumoconiosis.